Plant regeneration from long-term callus culture of AAA-group dessert banana - Conceição, Alexandre da Silva; Matsumoto, Kazumitsu; Bakry, Frederic; Bernd-Souza, Regina Beratriz (Pesquisa Agropecuaria Brasileira, 1998)
The banana plant is one of the most widely cultivated crops in the world. However, banana breeding has been a slow process, due to the low seed set and low germination rates. Selection of useful somaclonal variations and genetic transformation in cells or calluses are promising techniques to accelerate the breeding process. Therefore, callus culture was carried out, aiming the establishment of one protocol for plant regeneration, to be used in banana breeding program. Leaf sheath disks of 'Nanicão' banana (Musa sp., AAA group, Cavendish subgroup) were cultured on a Murashige and Skoog (MS) basal medium supplemented with activated charcoal (0.2 %), MES (2 [N-morpholino] ethanesulfonic acid) (15.3 mM), arginine (300 mM), Picloram (414 mM) and 2iP (2-isopentenyl adenine) (492 mM). Globular calluses developed on the leaf tissue were subcultured in the same medium, acquiring a friable and translucid appearance after one and a half year of culture. The friable calluses were transferred to the medium without growth regulators and arginine, and supplemented with casein hydrolysate (0.05%), where they formed embryo-like structures after transference to light. From these structures, shoots with roots were obtained and plantlets developed. The plant regeneration protocol shown here may be useful to banana breeding via somaclonal variation.